2015
DOI: 10.1016/j.ijdevneu.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and degenerative modulation of GABAergic transmission in the mouse hippocampus

Abstract: γ-Aminobutyric acid (GABA) is the main inhibitory neurotransmitter involved in synaptic plasticity. GABAergic transmission is also implicated in developmental and degenerative processes in the brain. The goal of the present study was to understand the developmental and degenerative regulation of GABAergic transmission in the mouse hippocampus by examining changes in GABA receptor subunit mRNA levels and GABA-related protein expression during postnatal development of the hippocampus and trimethyltin (TMT)-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…We found that the GABAergic neurotransmission counteracts spatial memory and LTP in the hippocampus. A critical role of the GABAergic transmission in memory formation and synaptic plasticity has been already described (Bonansco & Fuenzalida, 2016; Kim, Son, et al, 2015). Also, Hu et al demonstrated that chronic stress increases GABAergic transmission in the hippocampus (Hu et al, 2010).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We found that the GABAergic neurotransmission counteracts spatial memory and LTP in the hippocampus. A critical role of the GABAergic transmission in memory formation and synaptic plasticity has been already described (Bonansco & Fuenzalida, 2016; Kim, Son, et al, 2015). Also, Hu et al demonstrated that chronic stress increases GABAergic transmission in the hippocampus (Hu et al, 2010).…”
Section: Discussionmentioning
confidence: 81%
“…GABA, the main inhibitory neurotransmitter of the brain, has an essential role in learning and memory processes (Bonansco & Fuenzalida, 2016) as well as synaptic plasticity (Kim, Son, et al, 2015). Plenty of GABAergic interneurons are nested in hippocampus (Somogyi & Klausberger, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Allopregnanolone is a positive modulator of GABAAR activity [ 5 ]. GABA is the primary inhibitory neurotransmitter in the brain and plays a vital role in learning and memory [ 46 ] and synaptic plasticity [ 47 ]. The hippocampus has numerous GABAA receptors that participate in molecular mechanisms of memory formation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relative expression of genes was determined using the 2 -ΔΔct method with normalization to GAPDH expression. The primer sets used for D1R , D2R , GABA A R-α2 , GABA A R-α4 , GluR1 , GluR2 , NR2A, and NR2B were designed according to the publications ( Kim et al, 2010 , 2015 ; Zhou et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%